2013
DOI: 10.1159/000354504
|View full text |Cite
|
Sign up to set email alerts
|

Lacidipine Attenuates Apoptosis via a Caspase-3 Dependent Pathway in Human Kidney Cells

Abstract: Background: Acute kidney injury (AKI) is common in hospitalised patients and has a poor prognosis. Therefore, new therapeutic strategies are anticipated. Lacidipine, a novel third-generation dihydropyridine calcium channel blocker, has been demonstrated effective for hypertension. However, its potential effect on renal injury remains unknown. In the present study, an in vitro model of renal ischemia reperfusion (I/R) injury was used to investigate the protective effect and underlying mechanisms of lacidipine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Among the apoptotic mediators, activated caspase-3 acts as a final executor, as it regulates the extrinsic and intrinsic pathways of apoptosis (18,19). Furthermore, caspase-3-mediated cell apoptosis has been demonstrated to be essential in I/R-induced organ damage (20); thus, the effect of glycyrrhizin on I/R-induced renal cell apoptosis was investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Among the apoptotic mediators, activated caspase-3 acts as a final executor, as it regulates the extrinsic and intrinsic pathways of apoptosis (18,19). Furthermore, caspase-3-mediated cell apoptosis has been demonstrated to be essential in I/R-induced organ damage (20); thus, the effect of glycyrrhizin on I/R-induced renal cell apoptosis was investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…4 In addition, it was suggested that LCDP can protect the patients' kidney cells from apoptosis induced by adenosine triphosphate (ATP) depletion and their recovery by regulating the caspase-3 pathway. 5 Furthermore, LCDP was found to protect stroke-prone hypertensive rats against the impairment of endothelium-dependent vasorelaxation, evoked by a salt-rich diet, which may contribute to its beneficial effect against end-organ damage and stroke. 6 Finally, recent studies have confirmed its significance as an antibacterial and antitoxic compound.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, LCDP is an attractive therapy agent for the long-term management of essential hypertension. , As with other members of its class, it has shown potentially beneficial anti-atherosclerotic properties by affecting cellular cholesterol metabolism . In addition, it was suggested that LCDP can protect the patients’ kidney cells from apoptosis induced by adenosine triphosphate (ATP) depletion and their recovery by regulating the caspase-3 pathway . Furthermore, LCDP was found to protect stroke-prone hypertensive rats against the impairment of endothelium-dependent vasorelaxation, evoked by a salt-rich diet, which may contribute to its beneficial effect against end-organ damage and stroke .…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that benidipine reduces apoptosis and necrosis when modeling conditions of ischemia–reperfusion in experiments in vivo [ 31 , 32 ]. A similar effect is manifested by the action of lacidipine, a blocker of slow calcium channels from the group of dihydropyridine derivatives, when ATP is depleted in the epithelial cells of the renal tubules [ 33 ], and also when adding verapamil to ischemic intestinal epithelial cells. In the latter case, the activation of the mechanisms of cell death is associated with a change in the distribution of integrins and depolymerization of F-actin [ 34 ].…”
Section: Discussionmentioning
confidence: 94%